In vitro and in vivo evaluation of a photosensitive polyimide thin-film microelectrode array suitable for epiretinal stimulation - Jiang, Xia (BioMed Central, 2013)
BACKGROUND: Epiretinal implants based on microelectro-mechanical system (MEMS) technology with a polyimide (PI) material are being proposed for application. Many kinds of non-photosensitive PIs have good biocompatibility and stability as typical MEMS materials for implantable electrodes. However, the effects of MEMS microfabrication, sterilization and implantation using a photosensitive polyimide (PSPI) microelectrode array for epiretinal electrical stimulation has not been extensively examined. METHODS: A novel PSPI (Durimide 7510) microelectrode array for epiretinal electrical stimulation was designed, fabricated based on MEMS processing and microfabrication techniques. The biocompatibility of our new microelectrode was tested in vitro using an MTT assay and direct contact tests between the microelectrode surface and cells. Electrochemical impedance characteristics were tested based on a three-electrode testing method. The reliability and stability was evaluated by a chronic implantation of a non-functional array within the rabbit eye. Histological examination and SEM were performed to monitor possible damage of the retina and microelectrodes. Electrically evoked potentials (EEPs) were recorded during the acute stimulation of the retina. RESULTS: The substrate was made of PSPI and the electrode material was platinum (Pt). The PSPI microelectrode array showed good biocompatibility and appropriate impedance characteristics for epiretinal stimulation. After a 6-month epiretinal implantation in the eyes of rabbits, we found no local retinal toxicity and no mechanical compression caused by the array. The Pt electrodes adhesion to the PSPI remained stable. A response to electrical stimuli was with recording electrodes lying on the visual cortex. CONCLUSION: We provide a relevant design and fundamental characteristics of a PSPI microelectrode array. Strong evidences on testing indicate that implantation is safe in terms of mechanical pressure and biocompatibility of PSPI microelectrode arrays on the retina. The dual-layer process we used proffers considerable advantages over the more traditional single-layer approach and can accommodate much many electrode sites. This lays the groundwork for a future, high-resolution retinal prosthesis with many more electrode sites based on the flexible PSPI thin film substrate.